Korean Journal of Chemical Engineering - Kim, Do-Heyoung.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Korean Journal of Chemical Engineering provides a global forum for the dissemination of research in chemical engineering. The Journal publishes significant research results obtained in the Asia-Pacific region, and simultaneously introduces recent technical progress made in other areas of the world to this region. Submitted research papers must be of potential industrial significance and specifically concerned with chemical engineering. The editors will give preference to papers having a clearly stated practical scope and applicability in the areas of chemical engineering, and to those where new theoretical concepts are supported by new experimental details. The Journal also regularly publishes featured reviews on emerging and industrially important subjects of chemical engineering as well as selected papers presented at international conferences on the subjects.
Keywords: Biotechnology; Chemical engineering; Catalysis; Materials science; Industrial Chemistry/Chemical Engineering; Catalysis; Materials Science, general; Biotechnology